Analisis Minat Menjadi Guru dan Persepsi Mahasiswa Tentang Profesi Guru Terhadap Keputusan Pemilihan Program Studi pada Mahasiswa Pendidikan Akuntansi Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Surakarta Angkatan 2014 - Widiarsih, Tika; , Dr. Wafrotur Rohmah, M.M (2017)
The purpose of this study was to determine to describe: (1) the influence of the interest to be a teacher to the decision of the selection of courses on Accounting Education students Faculty of Teacher Training and Education University of Muhammadiyah Surakarta force 2014. (2) student perception about teacher profession to decision of election of study program at student of Accountancy Education Faculty of Teacher Training and Education University Muhammadiyah Surakarta force of 2014. (3) interest to be a teacher and student perceptions about the profession of teachers to the decision of the selection of courses in Accounting Education students Faculty of Teacher Training and Education University of Muhammadiyah Surakarta force 2014.This type of research is quantitative. The population in this study is Student of Accounting Education FKIP UMS class of 2014 is 237 students with sample of 143 students taken by proportional random sampling technique by lottery. The data collection technique using questionnaires that have been tested by validity and reliability testing. Data analysis technique used is multiple regression analysis.Based on the multiple regression analysis obtained the following results;Y = 7,578 + 0,325X1 + 0,131X2. The conclusion that can be drawn from the equation is: 1) "There is an influence of interest in becoming teacher toward the selection decision of the study program" is acceptable. This is proven through hypothesis test (t test), which shows that the value of tcount > ttable is 6,225> 1,977 With probability significance value <0.05 ie 0.017 and effective contribution (SE) 4.9%. 2) "There is influence of student perception about teacher profession to decision of election of study program" is acceptable. This is proven through hypothesis test (t test), which shows that tcount> ttable is 2,424> 1,977 with probability significance value <0,05 is 0,017 and effective contribution (SE) 4,9%. 3) "There is an influence of interest in becoming teachers and students' perceptions of the teaching profession on the election decision of the study program" is acceptable. This is proven through hypothesis test (t test), which shows that the value of fcount> ftable is 26,505> 3,061 with probability significance value <0,05 is 0,000 with coefficient of determination ( ) 27,6% while the rest 73% influenced by Other variables beyond this study.